Estudo de óleos nativos da Amazônia (Babaçu e Andiroba): modificação química, caracterização e avaliação como biolubrificante - Cavalcante, Glene Henrique Rodrigues (2016)
Natural bases and alternative easy degradability have been employed in the petrochemical industry for polymer formulation, paints, foams, particularly lubricating oils and detergents, due to its viscous characteristics. The great advantage of renewable raw materials to replace fossil products prompted the study of viscosity of babassu oils (Orbignya phalerata) and andiroba (Carapa guianensis Aubl.) After chemical modifications. For characterization of the oils was conducted an interlaboratory program in vegetable oils. In this program, attended by 12 university laboratories and research centers in several states of Brazil. The consensus values after statistical treatment were considered to be the physical and chemical characteristics of the oils babassu oil and andiroba. The tests involved in the program were: acid number, kinematic viscosity, saponification value, moisture content, iodine index, peroxide index, oxidative stability, hydroxyl number, density and fatty acid content by gas chromatography. After characterization, the oils were subjected to chemical modifications (alkaline ethyl transesterification, epoxidation and hydroxylation in situ). The babassu oil did not show favorable characteristics for use as bio-lubricants, and even after the chemical changes proposed, there was no significant changes in their flow properties. The production of andiroba polyols has been optimized using the full factorial design star with 18 experiments, including two axial points and 4 replicates at the center point. The evaluation was based on the reduction of the degree of unsaturation monitored mainly by the increase in kinematic viscosity. The study of the conversion process was effective for the synthesis of polyols in different viscosity ranges, indicating the best conditions for obtaining polyols having flow characteristics compatible with commercial lubricants. The andiroba polyols were compared to commercial lubricants and base oil, with consistent results.